Conductive polymer mediated earth abundant Z-scheme g-C3N4/Fe2O3 heterostructure with excellent photocatalytic activity. Issue 37 (7th September 2022) - Liu, Yuxuan; Pan, Guang-Yu; He, Xiong; Li, Tao; Liu, Fu-Tian; Li, Kui
Abstract : The ternary Z-scheme g-C3 N4 /PPy/Fe2 O3 heterostructure photocatalyst with excellent photocatalytic hydrogen evolution activity was designed and fabricated with PPy supporting and confining the nanosized Fe2 O3 using a facile method. Abstract : Iron being the second most abundant metal on the surface of the earth (5.1%), size-confined iron-based photocatalysts are of particular importance for solar energy conversion. Herein, a ternary Z-scheme g-C3 N4 /PPy/Fe2 O3 heterostructure photocatalyst with PPy supporting and confining Fe2 O3 was designed and fabricated for hydrogen production using a facile method. The small particle size of Fe2 O3 (around 5 nm) improved the transport efficiency of charge carriers with the conductive PPy acting as a mediator, and the formation of the g-C3 N4 –Fe2 O3 Z-scheme heterostructure dramatically facilitated the photocatalytic activity. Consequently, the optimal g-C3 N4 –PPy–Fe2 O3 demonstrated an excellent photocatalytic hydrogen evolution activity, which was 120, 6.4 and 4.8 times larger than that of the pristine g-C3 N4 and g-C3 N4 singly loaded separately with PPy and Fe2 O3, respectively, and exhibited considerable H2 and H2 O2 production activity even in the absence of a sacrificial agent.